Upaya Pencegahan Demam Berdarah Dengue (DBD) Melalui Penerapan PHBS di Desa Teloko - Nur Asbon; Viona Dhelafinia; Hanney Putri Wijaya; Zulia Zulia; Aulia Aulia; Shinta Alfa Bella; Serlly Destiana; Siti Saharah; Tia Rahma Nabila; Novita Sari; Sintia Wati; Edo Adensi; Desta Ayu Setiawati (JURNAL PENGABDIAN KADER BANGSA, 2026)
Dengue hemorrhagic fever (DHF) is a disease caused by the dengue virus and remains a common public health problem, particularly during the rainy season and in environments with poor sanitasion. The habit of the teloko village community of disposing of a waste indiscriminately into rivers contributes to the rapid breeding of mostiquitoes as vectors of dengue transmission, one of the efforts to pravent DHF is the implementation of clean and healthy living behavior ( CHLB). This study aimed to improve and assess the knowledge and attitudes of 44 residents of teloko village regarding DHF prevention and the implementation of CHLB. The method used was a quasi-experiemn design with a one group pre -test and post- test approach. The activity was conducted through healt education sassioms followed by question and answer discussions involving 44 participants. The level of knowledge was measured using a structured questionnaire administered before ( pre- test ) and after ( post- test) in intervention. The results showed an improvement in the knowledge and understanding of the participants after the health education intervention. Therefore, it can be concluded that health education is effective in improving the knowledge and awareness of the teloko village community regarding DHF prevention and the implementation of CHLB.